Control of plasticity of high‑strength condition of cold‑formed pearlitic steel - V. P. Fetisov (Литьë и металлургия)
The relative narrowing of the heat‑treated pearlite steel billet characterizes the overall level of plastic and technological properties of the cold‑formed wire with large total compressions. The reduction of the interplate distance during heat treatment and during plastic deformation is increased, and the loss during repeated drawing of the plate structure with an increase in the density of dislocations inside the cells in ferrite and an additional decrease in the mobility of dislocations when they are blocked by carbon atoms during the decay of cementite reduce the plasticity of cold‑formed pearlite steel.